Performance of fire protective coatings in reinforced concrete elements submitted to high temperatures - Britez, Carlos Amado; Silva, V. P.; Carvalho, M.; Helene, Paulo (Revista ALCONPAT, 2019)
This article aims to compare different fire-resistant coating systems to 1.5 cm cover and one-year-old reinforced concrete elements for evaluating the performance of these systems by visual inspection and verification of internal temperature evolution after standard fire simulations under the ISO 834 curve by using thermocouples for a time of 120 minutes. The results showed very close correlations with the literature for cement-based mortar coatings, as well as other particularities about plaster coatings and the possibility of using intumescent paints as passive protection in reinforced concrete elements.